Ionic liquid 1-hexyl-3-methylimidazolium hexafluorophosphate, an efficient solvent for extraction of acetone from aqueous solutions - Saien, Javad; Badieh, Marjan Mohammadi Sarab; Norouzi, Mahdi; Salehzadeh, Sadegh (The Journal of chemical thermodynamics, 2015)
[Display omitted] •The use of HMIMPF6 as a green ionic was feasible in the extraction of acetone from water.•The binodal curves were determined by cloud point measurement method.•High level separation factor of acetone between the ionic liquid and water were achieved.•The thermodynamic properties of HMIMPF6 were obtained by the Density Functional Theory calculations.•The NRTL and UNIQUAC models were applied satisfactorily to correlate the equilibrium data. (Liquid+liquid) equilibrium (LLE) of the chemical system of {water+acetone+1-Hexyl-3-methylimidazolium hexafluorophosphate (HMIMPF6) ionic liquid} was studied at different temperatures of (293.2, 298.2 and 303.2)K and under atmospheric pressure of 81.5kPa. The results show that HMIMPF6 provides the acetone distribution coefficient and separation factor values within (0.8813 to 1.2351) and (3.0 to 54.4), respectively; indicating the high capability of the ionic liquid for extraction of acetone from aqueous solutions. In most cases, acetone solubility in the ionic liquid is higher than in water, especially at higher solute concentrations. Meanwhile, higher separation factor is relevant to the lower temperature due to lower (water+ionic liquid) miscibility. The consistency of tie line data, at each temperature, was examined with Othmer–Tobias correlation. The values were nicely reproduced with the well-known NRTL and UNIQUAC models. Accordingly, the required thermodynamic properties of HMIMPF6 were obtained by the Density Functional Theory (DFT) calculations, carried out at the M06/6-311++G∗∗ level of theory. The root mean square deviations (RMSD) between experimental and model concentration values were 0.0192 and 0.0255, respectively; indicating close agreement of the both models.